The The Relationship Between Prosocial Behavior and Psychological Well-Being: A Case Study of Volunteers in Surabaya - Aulia, Af'ida (Yayasan Abdurrauf Cendekia Nusantara, 2025)
This article explores the relationship between prosocial behavior and psychological well-being in the context of volunteers in Surabaya. Although volunteer activities provide meaning and satisfaction, many volunteers experience psychological pressure due to a lack of support and appreciation. This is closely related to Carol Ryff’s concept of psychological well-being, which emphasizes a meaningful life and personal growth (eudaimonia). The study aims to analyze the relationship between prosocial behavior and psychological well-being among Gesit volunteers under the supervision of kitabisa.com, using a quantitative research method. Participants aged 20–40 were selected based on specific criteria, and psychological well-being was measured using an instrument based on Ryff’s six dimensions. The results of the study indicate that the higher an individual’s prosocial behavior, the higher their level of psychological well-being. Acts of helping others voluntarily and selflessly not only benefit the recipients but also serve as a source of psychological well-being for the helpers themselves. In the context of volunteering, altruistic motivation and empathy strengthen social relationships, give life meaning, and support personal development—three core dimensions of Carol Ryff’s theory of psychological well-being. These findings align with previous theories that emphasize the reflective and therapeutic nature of prosocial behavior, providing individuals with a sense of value and connection with others. Therefore, consistent engagement in prosocial behavior can serve as a pathway to achieving optimal psychological well-being and is relevant both academically and practically in designing sustainable volunteer development programs.